2019
DOI: 10.1038/s41433-019-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ocular torsion between congenital and acquired unilateral superior oblique palsy

Abstract: Background/Objectives To compare ocular torsion between congenital and acquired unilateral superior oblique palsy (USOP). Subjects/Methods Retrospective review was performed on medical records of 163 USOP patients. Qualitative fundus torsional states in both eyes were determined based on locations of optic disc and fovea. Disc-fovea angles (DFA) were collected in both eyes for quantitative analysis. DFAs and the proportions of qualitative fundus torsional states in paretic and non-paretic eyes were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In the study by Oh and Oh (10), all cases with decompensated causes were classified into the incomplete recovery group, and this may have influenced the higher vertical angle of deviation of the incomplete recovery group. These cases were not included in our study because decompensated palsy showed different clinical features and prognosis than those acquired palsies (13–15).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Oh and Oh (10), all cases with decompensated causes were classified into the incomplete recovery group, and this may have influenced the higher vertical angle of deviation of the incomplete recovery group. These cases were not included in our study because decompensated palsy showed different clinical features and prognosis than those acquired palsies (13–15).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, congenital unilateral SOP has been shown to cause higher fundus torsion than is acquired. Kim et al [ 8 ] showed that fundus torsion in congenital unilateral SOP is more common in nonparetic eyes. In the study by Kim et al [ 8 ], 61.1% of congenital unilateral SOP patients and 46.5% of acquired USOP patients showed extortion in both eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Lim [ 14 ] compared ocular torsion between patients with congenital and acquired unilateral SOP. In this study, patients with SOP had variable fundus torsion of varying etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients with SOP had variable fundus torsion of varying etiologies. They suggested that unilateral SOP might initially induce paretic ocular extorsion and then induce ocular dominance, cyclofusion, or a neural adaptation mechanism in the nonparetic eye, increasing the total amount of extorsion in both eyes [ 14 , 15 ]. We suspected that more severe nerve damage leads had a greater effect on compensatory ocular torsion mechanisms and results in more fundus extorsion in the nonparetic eye.…”
Section: Discussionmentioning
confidence: 99%